Global commodity chains, financial markets, and local market structures: Price risks in the coffee sector in Ethiopia - Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2015)
Risks related to commodity price volatility are a major thread to actors in commodity chains, particularly to smallholder farmers in low income countries. Therefore, price setting and transmission within global commodity chains are of crucial importance from a developmental and distributional perspective. With the end of global price stabilization mechanisms in the 1980s, financial derivative markets have taken over the central role in price discovery and risk management. This is also true for the case of coffee, being the agro-commodity with the highest trading volume on financial commodity exchanges. In this paper, the coffee commodity chain is assessed with a focus on Ethiopia, the largest coffee exporter in Sub-Saharan Africa. Given the crucial role of the coffee sector for exports and for millions of smallholders, price risks for Ethiopian and international actors are analyzed along two indicators - exposure to price risks and ability to mitigate price risks. Even though Ethiopia imposes strict regulations on local value addition in green coffee production, the use of a market-based price discovery system via the Ethiopian Commodity Exchange exposes local actors to highly volatile international coffee prices, but with limited access to risk management. This is in contrast to lead firms in the global coffee chain - international traders and roasters - which use various strategies to deal with and also profit from price risks, mainly interlinked to financial derivate markets.
Keywords: 330; global commodity chains; financialization; commodity prices; price risks; price risk management; coffee sector; Ethiopia; commodity exchange